Pelatihan Pengembangan Diri Seni Tari Pada Anak Tunarungu Di SLB Wacana Asih Kota Padang - Cici Aulia Sari; Herlinda Mansyur (SENDRATASIK UNP, 2019)
This article aims to describe the implementation of the training activities of self development in Deaf children dance on the SLB Discourse Compassion desert. This research is classified in qualitative research that uses descriptive approach. Instrument in this study is the researchers themselves by using data collection techniques in the form of observation, interview, documentation and study of the literature. The results showed that students can transmit an interest and talent in the art of dance in self development SLB Discourse Compassion desert. In the execution of training activities of self development in SLB Discourse Compassion field, teachers implement the method of demonstration, imitation method, manual methods or gestures. The main obstacle factors for Deaf students i.e. There is on the sense of hearing, but did not close the possibility for deaf children get his rights in education like other normal children. To develop the potential of deaf children much needed role of parents, families, teachers and the school of structural aid in the goal of self development close to the art of dance in the SLB Discourse Compassion desert.